Functional Implications of miR-19 in the Migration of Newborn Neurons in the Adult Brain - Han, Jinju; Kim, Hyung Joon; Schafer, Simon T.; Paquola, Apua; Clemenson, Gregory D.; Toda, Tomohisa; Oh, Jinseo; Pankonin, Aimee R.; Lee, Bo Suk; Johnston, Stephen T.; Sarkar, Anindita; Denli, Ahmet M.; et al. (Neuron, 2016)
Altered microRNA profiles have been implicated in human brain disorders. However, the functional contribution of individual microRNAs to neuronal development and function is largely unknown. Here, we report biological functions for miR-19 in adult neurogenesis. We determined that miR-19 is enriched in neural progenitor cells (NPCs) and downregulated during neuronal development in the adult hippocampus. By manipulating miR-19 in NPCs for gain- and loss-of-function studies, we discovered that miR-19 regulates cell migration by directly targeting Rapgef2. Concordantly, dysregulation of miR-19 in NPCs alters the positioning of newborn neurons in the adult brain. Furthermore, we found abnormal expression of miR-19 in human NPCs generated from schizophrenic patient-derived induced pluripotent stem cells (iPSCs) that have been described as displaying aberrant migration. Our study demonstrates the significance of posttranscriptional gene regulation by miR-19 in preventing the irregular migration of adult-born neurons that may contribute to the etiology of schizophrenia.
CRIS-Team Scopus Importer:2022-09-26
Keywords: adult neurogenesis; cell migration; hippocampus; human induced pluripotent stem cells (iPSCs); microRNA (miRNA); microRNA in vivo functions; miR-19; neural progenitor cells (NPCs); polycistronic microRNAs; Rapgef2; schizophrenia